Analysis of Anaerobic Digestion Installation Testing for Tofu Liquid Waste Utilization into Biogas with the Addition of Cow Manure Variations - Purboyo, Prido Dwi; Fahruddin, A’rasy (Indonesian Journal Publisher, 2024)
The purpose of this study is to convert tofu wastewater into biogas using an anaerobic digester with varying cow dung mixtures (10%, 15%, and 20%). The study method entails creating digesters including independent, dependent, and controlled variables. Variations in pH, temperature, biogas pressure, and biogas volume were detected throughout the course of a 15-day fermentation. The data show that in the 10% fluctuation, the greatest pH was on day 7 (7), whereas the highest temperature was 32°C on days 6 and 7. Biogas pressure emerged on day 6 (89.2 cmHg), resulting in a volume of 90 liters by day 15. In the 15% variation, the highest pH (7.2) occurred on day 8, with the highest temperature (34°C) on days 9 and 10. Biogas pressure began on day 5 (89.9 cmHg), with a biogas volume of 95 liters on day 15. The 20% variance resulted in the highest pH (7.4) on day 8 and the highest temperature of 35°C from days 9-11. Biogas pressure began on day 5 (90.7 cmHg), resulting in a biogas volume of 100 liters on day 15. This study sheds light on how to manage tofu waste into biogas with varying degrees of effectiveness and efficiency.